WeB-CEPT : a content creation tool for English Language teaching / Mohamed Amin Embi and Afendi Hamat - Embi, Mohamed Amin; Hamat, Afendi (Academy of Language Studies & UPENA, 2005)
Although e-learning is more available than before with the advent of Learning Networks, there is still a lack of localised tools for creating online language learning and teaching materials, especially for the teaching and learning of ESL in the Malaysian context. The purpose of this paper is to describe a 3-in-l tool known as WeB-CEPT (http://www.eltrec.ukm.my'/add modules.asp) designed to assist ESL teachers create, edit and publish online language learning and teaching materials. WeB-CEPT which is the acronym for Web-Based Creating, Editing and Publishing Tool is a Content Creation Tool (CCT) that enables ESL teachers to create WYSIWYG (What-You-See-Is-What'You-Get) HTML documents online and save them into an educational portal known as ELT-TReC (ELTOnline Teacher Resource Center) developed by the authors: The documents may contain simple text formatting, hyperlinks and images. WeB-CEPT also offers ESL teachers the ability to switch between WYSIWYG view and HTML code view. This enables teachers proficient with HTML to directly edit their contents in the WeBCEPT work area.